2021
DOI: 10.1007/s10672-021-09372-4
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Screening and Procedural Justice: Towards Fairer Use of Social Media in Selection

Abstract: Companies have started using social media for screening applicants in the selection process. Thereby, they enter a low-cost source of information on applicants, which potentially allows them to hire the right person on the job and avoid irresponsible employee behaviour and negligent hiring lawsuits. However, a number of ethical issues are associated with this practice, which give rise to the question of the fairness of social media screening. This article aims to provide an assessment of the procedural justice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 110 publications
0
3
0
1
Order By: Relevance
“…Therein, our article contributes to the literature in several ways: First and foremost, our results challenge the view that social media screening as such represents a socially irresponsible practice: It appears that social media screening has become more professional and mindful since Clark and Roberts criticised the practice in 2010 for transgressing the boundaries between private and professional life. Our study agrees with authors like Kluemper et al (2015) and Vosen (2021) concluding that applicants may not always react negatively to social media screening, depending on the way it is performed.…”
Section: Discussionsupporting
confidence: 93%
“…Therein, our article contributes to the literature in several ways: First and foremost, our results challenge the view that social media screening as such represents a socially irresponsible practice: It appears that social media screening has become more professional and mindful since Clark and Roberts criticised the practice in 2010 for transgressing the boundaries between private and professional life. Our study agrees with authors like Kluemper et al (2015) and Vosen (2021) concluding that applicants may not always react negatively to social media screening, depending on the way it is performed.…”
Section: Discussionsupporting
confidence: 93%
“…But despite these benefits, the process of social profiling can raise a range of potential ethical, legal, and privacy concerns. To start with, the use of social media in recruiting may strengthen digital inequality by excluding job seekers who are not active social media users (Karaoglu et al, 2021; Ruggs et al, 2016; Vosen, 2021). Various sociodemographic factors, such as age, race, education, and income, may lead to differential use of social media (Karaoglu et al, 2021).…”
Section: Potential and Pitfalls Of Social Profilingmentioning
confidence: 99%
“…Because employers are justifiably concerned that traditional selection methods (résumés, cover letters, and interviews) are vulnerable to deception via impression management tactics, which could exaggerate or obscure job-relevant KSAOs, using social media information to assess applicants provides a potential solution to balance hiring the "right" person while avoiding negligent hiring lawsuits (Berkelaar, 2014;Vosen, 2021). However, lacking structure or regulation, using social media information to assess applicants may blur ethical and legal lines regarding privacy while indirectly facilitating employment discrimination, as protected statuses may be observed online (Hoek et al, 2016;SHRM, 2016;Vosen, 2021). Stamper (2010) found that 45% of 2,600 U.S. hiring managers used social media information in selection and that 35% of this group rejected candidates based on the information yielded from social media.…”
Section: Implications For Adverse Impact and Protected Groupsmentioning
confidence: 99%
“…Using social media information to assess applicants also highlights the digital divide, how the use of and access to the internet varies across demographics such as age, gender, and race, which could perpetuate hiring discrimination (Alexander et al, 2019;Roth et al, 2016;Vosen, 2021). Popular press suggests that applicants with a social media presence may be viewed more positively than those without because the absence of online information may lead to uncertainty about certain attributes or qualifications of an applicant (Hill, 2012).…”
Section: Implications For Adverse Impact and Protected Groupsmentioning
confidence: 99%